Kelayakan Pengembangan Usaha Budidaya Ikan Pada Keramba Jaring Apung di Waduk Cirata - Gandhy, Abel (Agregat: Jurnal Ekonomi dan Bisnis, 2018)
The aim of this research is to analyze the impact of business development in term of diversification fish species cultivation in floating cage at Cirata Reservoir. Indicator of feasibility study based on Net Present Value (NPV), Internal Rate of Return (IRR), Pay Back Period (PP) and Net B/C. The research showed that diversification activities increases NPV Rp 157.420.576, raise IRR for 38%, Accelerate the payback period for 3 months and increases the Net B/C from 2,06 to 3,28. Therefore, diversification type of fish cultivation is recomended to apply because will increasing farmer income.